ISOLATION STUDIES ON THE PREVELANCE OF SALMONELLAE IN CHICKEN ORGANS, EGGS AND FEED COMPONENTS - Sajid, Saraj Uddin; Sajid, Mahum; Hashmi, Ramiz Iqbal (Journal of Ayub Medical College Abbottabad, 2015)
Background: Salmonella is an important zoonotic pathogen and its prevalence in the chicken meat and eggs acts as a continuous threat to human population. The current studies covering a time period of three years, was carried out to report the isolation of salmonellae from the chicken tissues, eggs and feed ingredient. Methods: A total of 1747 random samples from twelve different sources and 56 locations in Islamabad and Northern Punjab area of Pakistan, were screened for isolation studies according to the already published established protocols. Results: The analysis of 1747 random samples comprising of 1069 (61.19%) chicken organs and 678 (38.81%) allied sources including eggs and feed ingredients, showed that a total of 162 (9.27%) were positive for salmonellae. Isolation prevalence in various chicken organs and allied sources was 86 (8.04%) and 76 (11.20%) respectively. The maximum isolation prevalence was recorded in meat meal (19.35%), followed by fish meal (17.54%), hatchery fluff (14.63%), livers (13.17%), poultry litter (10.89%), and eggs (9.64%). The range of Salmonella isolated varied from 19.35% to 4.72% in various organs and allied sources. Conclusions: Our findings highlighted a potential public health hazard and emphasized the significance of continuous surveillance system in the country to understand the ever changing epidemiological pattern of Salmonella serovers. The endemic prevalence of various serovars can cause outbreaks of human salmonellosis due to the consumption of contaminated meat and eggs as has already been reported worldwide